Nature connection through film: Two films and some notes - Breden, Andreas (Murmurations: Journal of Transformative Systemic Practice, 2021)
These notes accompany two films that I have made. They are an attempt to punctuate why my connection to nature is so important to me and try to find a way to share this. I write attempt because I believe that we as human beings are ever-evolving, ever-revealing and ever-growing, and so is our relationship and connection to nature. It’s not a circular movement, but more like a spiraling one which adds one more dimension. We come back to places that are familiar but slightly different. What can we co-learn from lighting a campfire? https://youtu.be/NyBPVkhQjOY Following a stream towards the sea https://youtu.be/r7W7vF2dqzI